การเพาะเลี้ยงเนื้อเยื่อว่านสี่ทิศ และบอนสีในสภาพปลอดเชื้อ: In vitro culture of Hippeastrum johnsonnii Bury and Caladium bicolor Vent - Buddharaksa, Phopgao; Kaewdungtip, Chintana; U-Kong, Warut (Asian Health, Science and Technology Reports, 2011)
In vitro culture of to be Hippeastrum johnsonnii Bury. and Caladium bicolov Vent. The bulbscales explants were surface sterilize with clorox 10 percent for 10 min followed by clorox 20 percent 5 min, explants were 85.71 percent free from contamination. The sterilized bulbscales explants were culture on modified MS medium supplemented with Naphthalenecetic acid (NAA) at concentration of 1.0 mg/l. with N6-benzyl adenine (BA) at 0.5, 0.7, and 2 mg/l. The results showed that modified MS medium concentration BA 1.0 mg/l and NAA 2.0 mg/l were the best for induction shoots and plantlets with 6 weeks and grow well under environment with heights percentage of 80. In vitro culture of Caladium bicolor young leaf explants were sterilize with clorox 10 percent for 10 min to be followed by clorox 5 percent for 5 min resulted in success 80 percent. The sterilized young leaf explants were culture on modified MS medium supplemented with BA of the concentration 0.1,0.5,1.0 mg/l. and NAA 2 mg/l. The result showed that modified MS medium concentration of BA 0.5 mg/l with NAA 2 mg/l was the best for induction mean number of shoot averaged of 12 shoot per explants. Plantlets transferred to greenhouse condition at for 6 weeks of culture period were found to be 80 percent survival.